Complex assembly from planar and twisted π-conjugated molecules towards alloy helices and core-shell structures. Issue 1 (December 2018) - Lei, Yilong; Sun, Yanqiu; Zhang, Yi; Zhang, Hongyang; Zhang, Haihua; Meng, Zhengong; Wong, Wai-Yeung; Yao, Jiannian; Fu, Hongbing
Abstract Integrating together two dissimilar π-conjugated molecules into controlled complex topological configurations remains a largely unsolved problem owing to the diversity of organic species and their respective different assembly features. Here, we find that two structurally similar organic semiconductors, 9, 10-bis(phenylethynyl)anthracene (BA) and 5, 12-bis(phenylethynyl)naphthacene (BN), co-assemble into two-component helices by control of the growth kinetics as well as the molar ratio of BA/BN. The helical superstructures made of planar and twisted bis(phenylethynyl) derivatives can be regarded as (BA)x (BN)1−x alloys, which are formed due to compatible structural relationship between BA and BN. Moreover, epitaxial growth of (BA)x (BN)1−x alloy layer on the surface of BA tube to form BA@(BA)x (BN)1−x core-shell structure is also achieved via a solute exchange process. The precise control over composition and morphology towards organic alloy helices and core-shell microstructures opens a door for understanding the complex co-assembly features of two or more different material partners with similar structures. Manipulating the assembly of π-conjugated organic molecules into alloys to control composition and shape remains a largely unsolved problem. Here the authors show the co-assembly of two structurally similar organic semiconductors into two-component helices by control of their growth kinetics as well as the molar ratio of the building blocks.